Evaluation of treatment results in patients with early glottic cancer (stage T1aN0, T1bN0) treated with Manchester irradiation modality - Przeorek, Wiesława; Składowski, Krzysztof; Przeorek, Cezary (Contemporary Oncology/Współczesna Onkologia, 2007)
Data charts of 64 patients with stage I glottic cancer treated with Manchester irradiation modality in the 1st Radiotherapy Clinic of MSC Memorial Institute in Gliwice has been retrospectively analyzed. There were 55 males and 9 females at median age 63 years (range from 37 to 83 years). In 40 (62%) patients pathological subtype of squamous cell cancer has not been established. In 19 (30%) patients microscopic examination revealed keratinizing and in 5 (8%) non-keratinizing type of neoplasm. In 49 (77%) patients the tumour involved only one vocal cord, in 11 (17%) both, in 3 (5%) vocal cord and commissure and 1 (1%) patient both cords and commissure. All patients were treated with 60Co machines (36 patients – 56%) or high energy photons (28 patients – 44%). Radiotherapy was conducted with so-called Manchester modality with one daily fraction of 3Gy to a total dose of 51-54 Gy. Overall treatment time varied between 21 and 23 days. Acute mucosal reaction was evaluated with the morphological-functional Dische scale as well as with the EORTC/RTOG scoring system. The criteria of treatment efficacy were: 5-year local control, 5-year survival without serious complications (3 and 4 EORTC) and 5-year survival after salvage surgery in relapsed patients. In 63 patients complete regression of the tumour was observed up to 6 months of follow-up. One patient failed at the time of radiotherapy ending. In one case distant metastases to lungs were noticed. In 6 patients local relapses were discovered of which 3 were successfully salvaged with the surgery. In one patient, 18 months after radiotherapy massive oedema of laryngeal mucosa occurred. In this case tracheostomy was needed. 5-year local control, local control after salvage surgery and survival without serious complication rates are 89%, 97% and 95% respectively. 1. Radiotherapy with Manchester modality is a safe and effective treatment of stage I glottic cancer. 2. Despite hypofractionation the risk of severe complication is comparable to conventional irradiation to 60 Gy in 30 fractions. 3. Because of shorter overall treatment time this modality might be recommended in cases of early glottic cancer. 4. After radiotherapy the function of the larynx is preserved.